Produção intelectual sobre educação no período ditatorial : uma análise a partir de textos publicados na SciELO - Viana, Thais de Biagi (2017)
This research had as general objective to enable a mapping of texts on education in the period of civil-military dictatorship, published in SCIELO database in the period between 1985 and 2016, publication dates of the first and last text located. The methodological procedures were performed by bibliometric approach, focused on documentary research, with a descriptive and exploratory character. Based on professional literature, the data were analyzed and presented in order to facilitate the identification of the following: geographic and institutional distribution of localized journals; recurrent authors; institutional origin of the authors and their participation in research groups; themes addressed in the texts; and which aspects were addressed in the texts that are included in the thematic axis "educational policy". It is understood that the results of the search will enable contributions to the History of Education, because besides the historical review and mapping of knowledge that is being produced on an extremely relevant theme to the educational field, it allows the dialogue with the current educational conditions, such as wage squeeze, poor structure of teacher training courses, close link between education and the labor market, fundaments of school management, valuation of private initiatives, etc.